2013
DOI: 10.1002/jgra.50565
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the location of polar cusp in the Lyon‐Fedder‐Mobarry global magnetosphere simulation

Abstract: [1] In this paper we compare observations of the high-latitude cusp from DMSP data to simulations conducted using the Lyon-Fedder-Mobarry (LFM) global magnetosphere simulation. The LFM simulation is run for the 31 August 2005 to 02 September 2005 moderate storm, from which the solar wind data exhibits a wide range of conditions that enable a statistical representation of the cusp to be obtained. The location of the cusp is identified using traditional magnetic depression and plasma density enhancement at high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 44 publications
5
41
0
Order By: Relevance
“…The similarities give credence to mechanisms for generation of small‐scale Alfvén waves via a cascade of large‐scale Alfvén waves to dispersive scales (section 3 and references therein), since the altitude range and scale sizes treated in the simulation are several times the altitude range and ∼10 times greater than the scale sizes deduced from FAST data. Both observation and simulation show that ϕ IMF orientations involving southward B z correspond to the highest IAW powers and 2–20 mHz Alfvén wave powers, and that B y ‐dominated ϕ IMF orientations correspond to preferential generation of wave power opposite the side of noon local time that is expected on the basis of statistics and simulation of the motion of the polar cusp (e.g., Zhou et al, ; Zhang et al, ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The similarities give credence to mechanisms for generation of small‐scale Alfvén waves via a cascade of large‐scale Alfvén waves to dispersive scales (section 3 and references therein), since the altitude range and scale sizes treated in the simulation are several times the altitude range and ∼10 times greater than the scale sizes deduced from FAST data. Both observation and simulation show that ϕ IMF orientations involving southward B z correspond to the highest IAW powers and 2–20 mHz Alfvén wave powers, and that B y ‐dominated ϕ IMF orientations correspond to preferential generation of wave power opposite the side of noon local time that is expected on the basis of statistics and simulation of the motion of the polar cusp (e.g., Zhou et al, ; Zhang et al, ).…”
Section: Discussionmentioning
confidence: 98%
“…Under duskward ϕ IMF (Figure a, right center panel) the primary loci of enhanced dayside IAW Poynting flux are located prenoon and postnoon, respectively, at ∼9.5 MLT and ∼13 MLT. The postnoon hot spot during dawnward IMF and midmorning hot spot during duskward IMF are on the side of noon opposite that of the polar cusp in each case: observations (Dunlop et al, ; Zhou et al, ) and simulation (Zhang et al, ) show that in the Northern Hemisphere during dawnward IMF the polar cusp (as identified by diamagnetic depression and direct‐entry precipitation) is statistically at prenoon local times, and during duskward IMF the polar cusp is statistically at postnoon local times, which is consistent with antiparallel merging theory (Crooker, ). On the nightside, enhanced regions of IAW Poynting flux appear over ∼64–76° ILAT.…”
Section: High‐latitude Iaw Activity and Broadband Electrons As A Funcmentioning
confidence: 94%
“…The number flux of cusp outflow introduced in the numerical experiment is fixed in time, but its location varies dynamically as determined by a cusp identification algorithm derived from the density enhancement at 2.2 RE (geocentric) (Zhang et al, ). For the given SW/IMF conditions, the cusp outflow is mostly located on open field lines near 70° to 75° magnetic latitude and 1130–1230 MLT on the dayside, without significant changes in the cusp area due to the steady‐state upstream driving condition.…”
Section: Simulation Informationmentioning
confidence: 99%
“…The outflow patch is centered at noon, spanning 2.2 h in magnetic local time (MLT) and between magnetic latitudes of 73° to 76° at ionospheric altitudes (100 km). The measured cusp location in the LFM simulation for these solar wind driving conditions varies between 74° and 75° depending upon the method used to determine the center of the cusp [ Zhang et al , ]. The fixed location and extent of the cusp outflow patch are consistent with observations.…”
Section: Simulation Informationmentioning
confidence: 62%